Low-melting-point glass frit composition, as well as adhesive and coating material containing the same
A Li-free glass frit composition with controlled P/Al ratio and balanced alkali metal oxides addresses the cost and stability issues in ceramic production, providing stable adhesives and coatings with low moisture absorption.
Patent Information
- Application Number
- JP2023102897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-23
AI Technical Summary
The rising cost of lithium due to increased demand for lithium-ion batteries has led to higher manufacturing costs in the ceramic industry, and Li 2 O-free glass frit compositions suffer from poor storage stability due to moisture absorption, causing stickiness and affecting the production of adhesives and coatings.
A Li-free glass frit composition with a specific P/Al ratio of 0.6 to 1.5, balanced alkali metal oxide content (Na 2 O and K 2 O), and optional SiO 2 and B 2 O 3 components, which suppress moisture absorption and improve storage stability, maintaining low-temperature melting properties.
The composition achieves good storage stability with minimal moisture absorption, ensuring cost-effectiveness and maintaining low-temperature melting properties, suitable for adhesives and coatings.
Smart Images

Figure 2025002603000001 
Figure 2025002603000002 
Figure 2025002603000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a low melting glass frit composition and an adhesive and a coating material containing the same. [Background technology]
[0002] Currently, adhesives and coating materials containing ground glass frit are generally used as materials that adhere strongly to substrates, and adhesives and coating materials containing a low-melting glass frit composition are preferably used to prevent deformation or loss of strength of the adherend or coated object.
[0003] For low-temperature melting, it is preferable to select a silicate, borate, or phosphate-based oxide as the network-forming oxide for the glass, and it is better not to use lead, bismuth, or zinc as the network-modifying oxide, which are harmful and lead to high costs, and it is preferable to use an alkali metal or an alkaline earth metal.
[0004] For example, the low-melting milky glass composition described in Patent Document 1 contains a phosphate-based glass as a network-forming oxide and an alkali metal oxide and / or an alkaline earth metal oxide as a network-modifying oxide. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Application Publication No. 62-3776 Summary of the Invention [Problem to be solved by the invention]
[0006] The low-melting milky glass composition described in Patent Document 1 uses a phosphate-based glass as a network-forming oxide, and Li2O, Na2O, and K2O are selected as alkali metal oxides. Examples 1 to 10 are disclosed as working examples, and all of the examples contain Li2O.
[0007] Lithium is widely used in the ceramics industry, including the production of ceramics and glazes, but in recent years, the price of lithium has been rising due to the growing demand for lithium-ion batteries. As the price of lithium raw materials rises, the manufacturing costs in the ceramics industry are also rising. Phosphate-based glass containing Li2O as a raw material has the characteristics of low melting point, low water absorption rate from air, and good storage stability. On the other hand, when Li2O is not included and only Na2O and K2O are used as raw materials, problems arise especially in terms of storage stability. The phenomenon of poor storage stability refers to the phenomenon in which glass frit absorbs moisture in the air and becomes sticky when stored.
[0008] An object of the present invention is to provide a Li-free low-melting glass frit composition which absorbs little moisture in the air and has good storage stability, as well as an adhesive and a coating material containing the same. [Means for solving the problem]
[0009] The present invention (1) is a Li-free glass frit composition obtained by firing and pulverizing a raw material containing the following components (A) to (D), the glass frit composition having a P / Al ratio of 0.6 to 1.5, and component (C) consisting of Na2O and K2O, with the Na2O content being 6.1 to 21.1 mol % and the K2O content being 12.7 to 27.7 mol %. (A) P2O5; 15.0-23.5 mol% (B) Al2O3; 15.5 to 24.0 mol% (C) R2O (total amount of Na2O and K2O): 32.4 to 36.2 mol% (D) F2: 10.0 to 25.0 mol%
[0010] In the present invention (1), the glass has a phosphate-based glass containing P2O5 as component (A) and Al2O3 as component (B) as the network-forming oxides, and therefore has a basically low melting property. In order to suppress the amount of moisture absorption and improve the water resistance, adjusting the P / Al ratio is effective for improving the water resistance. If the amount of component (A) is too much, the water resistance is deteriorated, but conversely, if the amount is too little, a phenomenon occurs in which vitrification is difficult. If the amount of component (B) is too little, the water resistance is poor. If the amount of component (B) is too much, a phenomenon occurs in which phase separation occurs. Phase separation is an undesirable phenomenon in which a single-phase glass separates into two or more types of glass phases in a temperature range below the liquidus temperature.
[0011] A P / Al ratio of 0.6 to 1.5 is preferable because it can improve water resistance while maintaining the low-temperature melting property. The upper limit is more preferably 1.4, even more preferably 1.3, particularly preferably 1.2, and even more particularly preferably 1.1. The lower limit is more preferably 0.7, even more preferably 0.8, and especially preferably 0.9.
[0012] Too much R2O, an alkali metal oxide (C), reduces water resistance, and too little raises the softening temperature, but because the material basically uses low-melting phosphate glass, the rise in softening temperature does not have much of an adverse effect. The component (C) is composed of Na2O and K2O, and it is preferable that the Na2O content is 6.1 to 21.1 mol % and the K2O content is 12.7 to 27.7 mol %. The lower limit of the Na2O content is generally more preferably 7.0 mol%, even more preferably 8.0 mol%, particularly preferably 9.0 mol%, even more particularly preferably 10.0 mol%, extremely preferably 12.0 mol%, and even extremely preferably 14.0 mol%. The upper limit of the Na2O content is more preferably 20.0 mol%, even more preferably 19.0 mol%, particularly preferably 18.0 mol%, and even more particularly preferably 17.0 mol%. The lower limit of the K2O content is more preferably about 14.0 mol%, even more preferably about 15.0 mol%, and particularly preferably about 16.0 mol%. The upper limit of the K2O content is more preferably 25.0 mol%, even more preferably 24.0 mol%, particularly preferably 22.0 mol%, even particularly preferably 21.0 mol%, extremely preferably 20.0 mol%, even extremely preferably 19.0 mol%, and even more extremely preferably 18.0 mol%.
[0013] If the F2 content of component (D) is high, the glass tends to crystallize and the low-melting properties deteriorate, but since a low-melting phosphate-based glass is basically used, the adverse effect of an increase in the softening temperature is not so great. Regarding water resistance, the content of component (D) is preferably 10.0 to 25.0 mol%, with the lower limit being more preferably 12.0 mol%, even more preferably 14.0 mol%, particularly more preferably 16.0 mol%, and even more particularly more preferably 18.0 mol%.
[0014] The present invention (2) relates to the glass frit composition of the present invention (1), wherein the raw material further contains the following components (E) and / or (F): (E) SiO2; 0 to 4.0 mol% (F) B2O3; 0 to 15.0 mol%
[0015] Component (E), SiO2, causes the softening temperature to rise if there is too much of it, but it also has the effect of improving water resistance. Component (F), B2O3, like component (E), causes the softening temperature to rise if there is too much of it, but it also has the effect of improving water resistance. The lower limit of the SiO2 content is more preferably about 1.0 mol%, even more preferably about 2.0 mol%, and particularly preferably about 3.0 mol%. The lower limit of the B2O3 content is generally, more preferably, 3.0 mol%, even more preferably, 6.0 mol%, particularly preferably, 9.0 mol%, and even particularly preferably, 11.0 mol%.
[0016] The present invention (3) is the glass frit composition of the present invention (1) or (2), which is stored for one week in a sealed container adjusted to a temperature of 20 to 25°C and a humidity of 80 to 90%, and has a weight increase due to moisture absorption of 15% or less.
[0017] The present invention (3) shows the performance of the glass frit composition of the present invention (1) or (2) with respect to water resistance. The glass frit composition of the present invention (1) or (2) does not contain moisture immediately after production. However, when stored in air, the components of the present invention (1) and (2) are changed by absorbing moisture in the air. The glass frit composition of the present invention (1) or (2) can suppress the weight increase to 15% or less even when stored for one week in a sealed container adjusted to a temperature of 20 to 25°C and a humidity of 80 to 90%.
[0018] The present invention (4) is a method for producing a glass frit composition, comprising the steps of mixing the components (A) to (D) of the present invention (1) to prepare a first raw material, melting the first raw material to prepare a molten liquid, quenching the molten liquid to prepare a glass frit, and pulverizing the glass frit to a predetermined average particle size.
[0019] The present invention (4) includes four steps, namely, a step of mixing and preparing the first raw material powder, a step of melting, a step of quenching and crushing, and a step of adjusting the average particle size, and thus a glass frit composition can be produced by such a simple method.
[0020] The present invention (5) is a method for producing a glass frit composition, comprising the steps of: mixing components (A) to (D) of the present invention (1) and components (E) and (F) of the present invention (2) to prepare a second raw material; melting the second raw material to prepare a melt; quenching the melt to prepare a glass frit; and pulverizing the glass frit to a predetermined average particle size.
[0021] The present invention (5) is the same as the present invention (4) except for the step of mixing and preparing the second raw material powder instead of the first raw material powder.
[0022] The present invention (6) is an adhesive or coating material comprising the glass frit composition of the present invention (1) or (2).
[0023] The glass frit composition of the present invention (1) or (2) has low melting properties, and therefore is unlikely to adversely affect the physical properties of the object even when it is mixed into an adhesive or coating material. In addition, the glass frit composition of the present invention (1) or (2) is a glass frit composition that absorbs less moisture in the air and has good storage stability, so that when an adhesive or coating material is produced, it is not necessary to pay much attention to the storage of the glass frit composition. Effect of the Invention
[0024] By using the low-melting glass frit composition of the present invention, it is possible to provide a glass frit composition which is cost-effective, absorbs less moisture in the air, and has good storage stability, a method for producing the same, and an adhesive and a coating material containing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Examples and comparative examples will be described below. The raw materials used to prepare the examples and comparative examples are shown in Table 1 below. [Table 1]
[0026] [How to make frit] 100 g of raw material powders that had been weighed to have a predetermined component ratio were mixed and placed in a chamotte crucible, and melted at a temperature of 1000° C. to 1300° C. for 5 minutes to 60 minutes to prepare a molten liquid. The resulting melt was poured onto a roll and quenched to form a frit.
[0027] [How to make frit powder] The resulting frit was pulverized using a ball mill so that the average particle size D50 became 4 to 20 μm. The average particle size D50 was confirmed to be 4 to 20 μm using a laser type particle size distribution measuring device.
[0028] [How to prepare disc-shaped pellets for evaluating firing characteristics] To investigate the firing characteristics of the glass frit, 2 g of the prepared frit powder was used to prepare a disk-shaped pellet with a diameter of 12 mm and a height of 14 mm. The applied pressure was 300 kg / mm. 2 It was decided.
[0029] [Methods for evaluating firing characteristics] The glass transition temperature (Tg) and the glass yield temperature (Td) were measured using a differential thermal analyzer (DTA).
[0030] The evaluation criteria are as shown in Table 2 below. [Table 2]
[0031] The components and properties of a glass frit composition containing Li2O as a reference example are shown in Table 3. The units of components are mol%, and the same applies to Tables 4 to 9 below. [Table 3] The glass was a phosphate-based glass containing Al2O3 and P2O5, and contained 12.2 mol% Li2O. The P / Al ratio was 1.2, and the content of alkali metal oxide R2O was 35.2 mol%. In the water resistance test, the weight gain was 3.6%, which was very good. The results of the differential thermal analysis test showed that both Tg and Td were good, and the sinterability was also very good. The results of this reference example showed that the inclusion of Li2O resulted in good results in all of water resistance, low-temperature melting property, and sinterability. It is believed that these properties are obtained by including Li2O in the phosphate-based glass.
[0032] The components and properties of glass frit compositions not containing Li2O are shown in Table 4 below as comparative examples and examples. The experimental system shown in Table 4 shows the results of changing the P / Al ratio by adjusting the contents of Al2O3 and P2O5. [Table 4] In the results of Examples 1 to 6, the water resistance was acceptable when the P / Al ratio was in the range of 0.6 to 2.0, but the low-temperature melting property and sintering property were unacceptable when the P / Al ratio was 2.0 (Comparative Example 3). In Comparative Examples 1 and 2, the water resistance, low-temperature melting property and sinterability were all rated as x, while in Comparative Example 3, the water resistance was rated as fair, within the acceptable range, but both the low-temperature melting property and the sinterability were rated as x. From these results, it is seen that the P / Al ratio is preferably 1.5 or less, P2O5 is preferably 15.0 to 23.5 mol %, and Al2O3 is preferably 15.5 to 24.0 mol %.
[0033] The following Table 5 shows the components and properties of glass frit compositions not containing Li2O as comparative examples and examples. The experimental system shown in Table 5 shows the results of changing the alkali metal oxide R2O. [Table 5] In the results of Examples 7 to 10, when the R2O content was in the range of 32.4 to 36.2 mol%, the water resistance was acceptable. The low-temperature melting property and sintering property were also acceptable. In Comparative Examples 4 and 5, the water resistance and low-temperature melting property were acceptable, but the sinterability was unacceptable. From these results, the R2O content is preferably in the range of 32.4 to 36.2 mol%, and more preferably 32.4 to 33.7 mol%.
[0034] The components and properties of glass frit compositions not containing Li2O are shown in the following Table 6 as comparative examples and examples. The experimental system shown in Table 6 shows the results when the component ratios of Na2O and K2O are changed while the alkali metal oxide R2O is kept constant. [Table 6] In the results of Examples 11 to 14, the water resistance, low-temperature melting property, and sinterability were all acceptable in all ranges. In Comparative Example 6, the water resistance and low-temperature melting property were acceptable, but the sinterability was unacceptable. From these results, it is seen that the Na2O content is preferably 6.1 to 21.1 mol %, and the K2O content is preferably 12.7 to 27.7 mol %.
[0035] The components and properties of glass frit compositions not containing Li2O are shown in the following Table 7 as comparative examples and examples. The experimental system shown in Table 7 shows the results when the P / Al ratio, R2O content, Na2O content, and K2O content are constant and the SiO2 component is changed. [Table 7] The results of Examples 15 to 17 showed that the water resistance, low-temperature melting property and sinterability were acceptable in all ranges. In Comparative Example 7, the water resistance and low-temperature melting property were acceptable, but the sinterability was unacceptable. From these results, it is apparent that the SiO2 content is preferably 0.0 to 4.0 mol %.
[0036] The components and properties of glass frit compositions not containing Li2O are shown in the following Table 8 as comparative examples and examples. The experimental system shown in Table 8 shows the results when the P / Al ratio, R2O content, Na2O content, K2O content, and SiO2 content are constant, and the B2O3 content is changed. [Table 8] The results of Examples 18 to 21 showed that the water resistance, low-temperature melting property and sinterability were acceptable in all ranges. In Comparative Example 8, the water resistance and low-temperature melting property were acceptable, but the sinterability was unacceptable. From these results, it is apparent that the B2O3 content is preferably 0.0 to 15.0 mol %.
[0037] The components and properties of glass frit compositions not containing Li2O are shown in the following Table 9 as comparative examples and examples. The experimental system shown in Table 9 shows the results when the P / Al ratio, R2O content, Na2O content, K2O content, SiO2 content, and B2O3 content are constant, and the F2 component is changed. [Table 9] In the results of Examples 22 to 25, the water resistance, low-temperature melting property, and sinterability were all acceptable in all ranges. In Comparative Example 9, the water resistance and low-temperature melting property were acceptable, but the sinterability was unacceptable. From these results, it is apparent that the content of F2 is preferably 10.0 to 25.0 mol %. [Industrial Applicability]
[0038] The glass frit composition of the present invention can be suitably used as a glass frit for adhesives and coating materials. In addition, since it has excellent water resistance, it can be easily stored and can be suitably used in production.
Claims
1. A Li-free glass frit composition obtained by sintering and pulverizing a raw material containing the following components (A) to (D), wherein the P / Al ratio is 0.6 to 1.5, and component (C) is Na 2 O and K 2 O and Na 2 The content of O is 6.1 to 21.1 mol %, and K 2 A glass frit composition having an O content of 12.7 to 27.7 mol %. (A) P 2 O 5 15.0 to 23.5 mol % (B) Al 2 O 3 15.5 to 24.0 mol % (C) R 2 O(Na 2 O and K 2 O total amount): 32.4 to 36.2 mol% (D) F 2 10.0 to 25.0 mol %
2. The glass frit composition according to claim 1 , wherein the raw material further contains the following components (E) and / or (F): (E) SiO 2 0 to 4.0 mol % (F) B 2 O 3 0 to 15.0 mol %
3. 3. The glass frit composition according to claim 1, wherein the glass frit composition has a weight increase of 15% or less due to moisture absorption when stored for one week in an airtight container adjusted to a temperature of 20 to 25° C. and a humidity of 80 to 90%.
4. A step of preparing a first raw material by mixing the components (A) to (D) according to claim 1; Melting the first raw material to form a melt; quenching the melt to form a glass frit; and crushing the glass frit to a predetermined average particle size.
5. A step of preparing a second raw material by mixing the components (A) to (D) according to claim 1 and the components (E) and (F) according to claim 2; Melting the second raw material to form a melt; quenching the melt to form a glass frit; and crushing the glass frit to a predetermined average particle size.
6. 3. An adhesive or coating material comprising the glass frit composition according to claim 1 or 2.
Citation Information
Patent Citations
Thawing of frozen food and apparatus for controlling same
JP1987003776A